2020
DOI: 10.4103/1319-4534.301296
|View full text |Cite
|
Sign up to set email alerts
|

Eye injuries caused by date palm thorns and leaves

Abstract: PURPOSE: To describe the clinical presentation, management, and outcome of hospitalized patients having date palm tree eye injuries. METHODS: This is a retrospective study of consecutive patients who were admitted to Al-Ain hospital following date palm tree eye injuries between 2012 and 2017. Patients' demography, symptoms and signs at presentation, surgical intervention, visual acuity (VA) before and after treatment, hospital stay, and causes for VA limitation were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It is estimated that there will be over 40 million date palm trees in the UAE. 31 Hence, an enormous amount of lignocellulosic biomass waste material is available in the form of leaves, fibers, date pits/stones, and stem waste. 32 Furthermore, it contains a plentiful amount of cellulose (30–45%), which is an advantage to isolate good yields of CNCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that there will be over 40 million date palm trees in the UAE. 31 Hence, an enormous amount of lignocellulosic biomass waste material is available in the form of leaves, fibers, date pits/stones, and stem waste. 32 Furthermore, it contains a plentiful amount of cellulose (30–45%), which is an advantage to isolate good yields of CNCs.…”
Section: Introductionmentioning
confidence: 99%
“…Annually, the United Arab Emirates (UAE) accounts for 14% of global total date fruit production. It is estimated that there will be over 40 million date palm trees in the UAE . Hence, an enormous amount of lignocellulosic biomass waste material is available in the form of leaves, fibers, date pits/stones, and stem waste .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of ocular injuries due to date palm thorns and prickly pear spine showed mostly these thorny fruits causing keratitis, corneal ulcer, and corneal perforation with no injury beyond the lens. Both studies also show that eye injuries occur mainly due to a lack of protective eyewear [ 6 , 7 ]. Our patient demonstrated severe ocular injury caused by durian.…”
Section: Discussionmentioning
confidence: 99%
“…The date palm (Phoenix dactylifera) is a flowering plant cultivated principally for eating its fruit. Date trees can reach lengths of 21 to 23 m, with leaves that can attain heights of 4 to 6 m and have about 150 leaflets each [1]. The trees typically grow individually or in clusters from a single root system.…”
Section: Introductionmentioning
confidence: 99%